2014
DOI: 10.1016/j.tjog.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of cumulus cells in women with poor ovarian response after dehydroepiandrosterone supplementation

Abstract: The study showed that DHEA therapy positively affected the gene expression of CCs in women with POR, and provided evidence to support the positive effect of DHEA supplementation on women with POR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…72e74 Thus, investigation of the effect of DHEA on gene expression of CCs may be a good idea to identify the exact mechanisms of DHEA in follicular microenvironment. 45 In our previous study, we found that DHEA supplementation might influence gene expression of CCs in women with POR, and these genes were involved in extracellular matrix formation, cell development, differentiation, and apoptosis regulation. Additionally, changes of the abovementioned genes favored the oocyte maturation.…”
Section: Further Workmentioning
confidence: 92%
See 1 more Smart Citation
“…72e74 Thus, investigation of the effect of DHEA on gene expression of CCs may be a good idea to identify the exact mechanisms of DHEA in follicular microenvironment. 45 In our previous study, we found that DHEA supplementation might influence gene expression of CCs in women with POR, and these genes were involved in extracellular matrix formation, cell development, differentiation, and apoptosis regulation. Additionally, changes of the abovementioned genes favored the oocyte maturation.…”
Section: Further Workmentioning
confidence: 92%
“…Additionally, changes of the abovementioned genes favored the oocyte maturation. 45 In conclusion, based on previous research, the effect of DHEA is believed to be mediated by androgen and IGF-1, although the exact mechanisms remain elusive. However, the effect of DHEA on gene changes of CCs may be a promising research field to explore the molecular mechanisms of DHEA on reproduction.…”
Section: Further Workmentioning
confidence: 95%
“…DHEA may improve ovarian function in women with poor ovarian response by activating anti-apoptotic processes in cumulus cells. These processes most likely involve the upregulation of genes related to extracellular matrix (ECM) formation and downregulating genes related to cell development, differentiation, and apoptosis (84). In other areas, DHEA supplementation has been reported to have an effect on regulation of the Th1/Th2 response.…”
Section: Balance Of the Th1 And Th2 Immune Responsementioning
confidence: 99%
“…Numerous studies indicate that gene expression in CCs can serve as biomarkers for oocyte or embryo quality and pregnancy outcomes 14-16. Our previous self-controlled studies demonstrated the potential anti-apoptotic effect on CCs following DHEA treatment 17, 18. Apoptosis plays a critical role on oogenesis, folliculogenesis, oocyte loss, selection, atresia and luteogenesis 19.…”
Section: Introductionmentioning
confidence: 97%
“…Based on our previous studies 17, 18 and the numerous studies discussed thus far, we hypothesized that DHEA may improve reproductive outcomes in PORs through increasing mitochondrial function and decreasing apoptosis in CCs. To verify this hypothesis, we compared the IVF outcomes of normal ovarian responders (NORs), PORs with or without DHEA supplementation and collected their CCs for researches.…”
Section: Introductionmentioning
confidence: 99%